AN ERROR ANALYSIS OF DESCRIPTIVE TEXTS WRITTEN BY FIRST-SEMESTER EFL STUDENTS: A SURFACE STRATEGY TAXONOMY APPROACH - Linda Meylinda (JEELL (Journal of English Education, Linguistics and Literature), 2026)
The present study sought to identify grammatical and syntactic errors in EFL students' descriptive writing. The study was conducted on the basis of the observation that first-semester students had recently encountered difficulties accurately applying English grammar in creative and descriptive contexts. Given the importance of English syntax in academic settings, this research was conducted at a private university in Tangerang Selatan. There were 10 participants in this study who were enrolled in the first semester and had recently completed descriptive writing assignments. To obtain accurate data, the researchers collected student-written descriptive essays through a qualitative study employing a case study design. The students were asked to produce texts describing themselves. These essays were then analyzed using the Surface Strategy Taxonomy proposed by James (1998) to identify, classify, and report linguistic patterns. Under this category, errors were classified into four types: omission, addition, misformation, and misordering. The result showed an interpretation of how students manipulate the surface structure of the target language. The findings of this research are expected to shed light on common issues and suggest that identifying these specific patterns is very influential in improving writing and confidence.